2003
DOI: 10.1152/ajpheart.00658.2002
|View full text |Cite
|
Sign up to set email alerts
|

Systemic α1A-adrenoceptor antagonist inhibits neointimal growth after balloon injury of rat carotid artery

Abstract: Previous in vitro and in vivo studies have shown that norepinephrine, acting through alpha(1A)-adrenoceptors, stimulates hypertrophy, proliferation, and migration of vascular smooth muscle cells and adventitial fibroblasts and may contribute to neointimal growth, lumen loss, and inward remodeling caused by iatrogenic wall injury and vascular disease. Our present aim was to determine whether intravenous administration of the alpha(1A)-adrenoceptor antagonist KMD-3213, at dosages without systemic hemodynamic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
35
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 27 publications
9
35
1
Order By: Relevance
“…Furthermore, other studies have revealed that the functional role of ␣ 1 -ARs in the cardiovascular system is not only vasoconstriction but also postnatal cardiac development (20). In addition, previous studies using rat aorta, artery, and cultured cells with selective ␣ 1 -antagonists have demonstrated that the activation of the ␣ 1 -AR subtype (particularly, the ␣ 1A -AR subtype, but not the ␣ 1D -AR subtype) can induce neointimal formation (10,12,36), even though the ␣ 1B -AR and ␣ 1D -AR subtypes were mainly expressed in the rat aorta at both the mRNA and protein levels (11). On the other hand, the exact functional role of ␣ 1B -AR subtypes in neointimal formation still remains unclear because of lack of appropriate ␣ 1B -selective antagonists and satisfactory methods of quantitative ␣ 1 -AR subtype mRNA expression analysis (10,36,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, other studies have revealed that the functional role of ␣ 1 -ARs in the cardiovascular system is not only vasoconstriction but also postnatal cardiac development (20). In addition, previous studies using rat aorta, artery, and cultured cells with selective ␣ 1 -antagonists have demonstrated that the activation of the ␣ 1 -AR subtype (particularly, the ␣ 1A -AR subtype, but not the ␣ 1D -AR subtype) can induce neointimal formation (10,12,36), even though the ␣ 1B -AR and ␣ 1D -AR subtypes were mainly expressed in the rat aorta at both the mRNA and protein levels (11). On the other hand, the exact functional role of ␣ 1B -AR subtypes in neointimal formation still remains unclear because of lack of appropriate ␣ 1B -selective antagonists and satisfactory methods of quantitative ␣ 1 -AR subtype mRNA expression analysis (10,36,41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies using rat aorta, artery, and cultured cells with selective ␣ 1 -antagonists have demonstrated that the activation of the ␣ 1 -AR subtype (particularly, the ␣ 1A -AR subtype, but not the ␣ 1D -AR subtype) can induce neointimal formation (10,12,36), even though the ␣ 1B -AR and ␣ 1D -AR subtypes were mainly expressed in the rat aorta at both the mRNA and protein levels (11). On the other hand, the exact functional role of ␣ 1B -AR subtypes in neointimal formation still remains unclear because of lack of appropriate ␣ 1B -selective antagonists and satisfactory methods of quantitative ␣ 1 -AR subtype mRNA expression analysis (10,36,41). As in a previous study using rat vessels (10,12,36), our study also showed that lack of the ␣ 1D -AR gene was not required to inhibit neointimal formation in the mouse femoral artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They show that eutrophic (collagen deposition and fibrosis) and hypertrophic (proliferation and migration of smooth muscle cells and of adventitial fibroblasts) remodelling characterizes the damages caused by catecholamines on the vascular wall (1,(4)(5)(6)(7)(8)(9). These observations have also been indirectly confirmed by using a-adrenoceptor antagonists (9)(10)(11)(12)(13) and by experiments in animals submitted to local or systemic sympathetic denervation (14). In humans, even in physiological conditions, the elevated catecholaminergic tone associated with aging increases vascular (femoral) wall thickness (28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in animal models employing balloon injury of the carotid or aorta, an exacerbation of this action may be observed with proliferation, hypertrophy and migration of smooth muscle cells and adventitial fibroblasts, leading to hypertrophic remodelling (1,(4)(5)(6)(7)(8)(9). The direct influence of sympathetic neurotransmitters on vascular wall structure has been supported by studies using a-adrenoceptor antagonists that showed a reduction in proliferation of vascular wall cells and in neointimal growth after vascular injury (9)(10)(11)(12)(13). Finally, these findings have also been confirmed by the suppression in wall growth observed after local or systemic sympathetic denervation in animal experiments (14).…”
Section: Introductionmentioning
confidence: 99%